Development of an Electrodialysis (ED) Desalination System Using Cement Mortar-Structured Zeolite Membranes from Corn Stover (Zea Mays) Ash - Pangan, Norway Josue (Animo Repository, 2022)
Zeolite A was synthesized from corn (Zea Mays) stover ash using a hydrothermal method. The corn stover ash and synthesized zeolite A were characterized by X-ray fluorescence (XRF), thermogravimetry (TG-DTA), Brunauer-Emmert-Teller (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The effects of calcination time, fusion ratios, and curing time were examined. The yield and cation exchange capacity (CEC) of the synthesized zeolite A were investigated using statistical test via the Response Surface Methodology employing a Central Composite Design through the multiple objective optimizations with desirability function. The obtained optimum parameters for the maximum % yield (75.08%) and CEC (2.282 meq/g) were as follows: calcination temperature (534.5oC), fusion ratios (1:1.708), and curing time (10.50 hours). The maximum overall desirability of 0.5970 was attained. Response surface methodology by a two-level full factorial central composite design optimized the binder ratios, applied voltage and cell pair for cement mortar-structured zeolite membrane employing synthesized zeolite A in hydrogen form (zeolite HA) in an electrodialysis (ED) desalination system. All of the variables examined, specifically the binder ratio (15.00%), the applied voltage (15.00V), and the number of stacked cell pairs (3 pairs) were found to have an influence on sodium ion removal (80.68%). The developed model enables prediction of the separation percentage of an ED cell under various operating conditions. In summary, an ED desalination system built on corn stover-based cement mortar-structured zeolite membranes was proven to be an efficient alternative method for treating saltwater or brackish water and ultimately producing fresh water. The study successfully demonstrated its aim to develop a technology application that is novel and is a potent alternative for an ED desalination system that is simple, economical, and readily available for rural communities to gain access to clean and freshwater.